FRI0491 Circulating dna changes in rheumatoid arthritis patients blood. (23rd January 2014) - Rykova, E.; Sizikov, A.; Antonenko, O.; Skvortsova, K.; Morozkin, E.; Vlassov, V.; Laktionov, P.; Kozlov, V.
Abstract : Background: Early diagnostics of rheumatoid arthritis (RA) is of importance for the effective recovery, which is hampered due to the unspecific clinical manifestations. One of the clinically used RA markers is the increased level of rheumatoid factor (RF), which is a set of antibodies against IgG Fc-fragment, but it is also found in other disorders. Elevated level of circulating extracellular DNA (cirDNA) concentration was earlier found in the blood plasma of systemic lupus erythematosis (SLE) patients and was associated with disease pathogenesis. Objectives: This study was to reveal the association of cirDNA concentration changes with rheumatoid arthritis development and progression. Methods: Blood samples were taken from 48 healthy subjects (HS) and 37 RA patients (ACR, 1987). Blood was fractionated, cirDNA was extracted from plasma and cell-surface-bound cirDNA (csb-cirDNA) fraction, which was obtained by successive treatment of blood cells with PBS/EDTA and trypsin solutions. CirDNA concentration was measured by quantitative real-time PCR specific for LINE-1 repetitive elements from genome DNA and a fragment from mitochondrial DNA (mitDNA). Rheumatoid factor titers were estimated using Latex Agglutination Kits (Olvecs Diagnosticum, St-Petersburg), anti-ssDNA, anti-dsDNA antibodies were estimated using ELISA Kits (Vector-Best, Novosibisk). Results: Reliable increase of the cirDNA from plasma is found for RA patients compared with healthy subjects (2.7 versus 1.6 ng/ml, Mann-Whitney U test, p<0, 01). Csb-cirDNA concentration in the blood from RA patients is significantly decreased (6.7 versus 13.4 ng/ml, p<0, 01). CirDNA changes are not associated with patient age, sex, disease progression. Reliable association of csb-cirDNA with RF level is found: csb-cirDNA concentration is significantly lower in patients with high RF titers (>1:1600) compared with median (1:400; 1:800, p<0, 05) and low (1:100; 1:200, p<0, 01) RF levels. Mitochondrial DNA concentration is not changed in blood plasma from RA patients compared with HS (156750 copies/ml versus 170560 copies/ml, p>0.05), whereas it is increased in the csb-cirDNA (444760 copies/ml versus 287800 copies/ml p<0, 05). Mitochondrial csb-cirDNA increase is associated with RA progression: II-III stage patients have significantly higher concentration compared with I-II stage patients (p<0, 01). The highest elevation of mitochondrial csb-cirDNA is found in the group of RA patients with median titers of rheumatoid factor (1:400; 1:800) compared with groups with low (1:100; 1:200, p<0, 01) and high RF titers (>1:1600, p<0, 01). It is also notable that mitochondrial csb-cirDNA is significantly elevated in the RA patients group which is characterized by presence of anti-ssDNA and/or anti-dsDNA antibodies compared with the RA group without anti-DNA antibodies (p<0, 05). Conclusions: Rheumatoid arthritis development is accompanied by changes of the circulating genome DNA and mitochondrial DNA concentrations, which are associated with the development of self-immune antibodies (anti-IgG Fc-fragment, anti-ssDNA, anti-dsDNA). Data obtained indicate the value of the cirDNA further study as a potential factor, applied for diagnostics, and possibly participating in the rheumatoid arthritis pathogenesis. Disclosure of Interest: None Declared